Development and synthesis of DNA-based label-free electrochemical biosensor for detection of Enterocytozoon bieneusi using screen-printed gold electrode - Sara Nemati; Amir Sadeghi; Seyyed Mehdi Khoshfetrat; Hanieh Mohammad Rahimi; Kobra Omidfar; Hamed Mirjalali (BMC Chemistry)
Abstract Microsporidia are a large group of obligate intracellular parasites. In this study, a label-free electrochemical genosensor was developed to detect Enterocytozoon bieneusi using specific probe and electrode substrate, Mxene-Ti3C2/AuNPs/PDA. A 5' thiol-modified DNA probe, targeting 16S like ribosomal RNA (rRNA) gene of E. bieneusi, was designed. The Ti3C2-AuNPs-PDA nanocomposite was synthesized. The surface modification of the screen-printed gold electrodes (SPGE) was characterized by cyclic voltammetry (CV) and differential pulse voltammograms (DPVs) electrochemical methods. Scanning electron microscopy (SEM), transmission electron microscopy (TEM), fourier transform infrared spectroscopy (FTIR), and energy dispersive X-ray analysis (EDX or EDS) were employed to analyze the nanocomposites. The functional groups of Ti3C2/AuNPs/PDA nanocomposite were characterized using FT-IR spectroscopy. The SEM analysis revealed a layered accordion-like architecture of Ti3C2. The TEM image confirmed the deposition of composite on the substrates. The EDS mapping showed the elemental content of AuNPs, Ti3C2/AuNPs, and Ti3C2/AuNPs/PDA. A decrease in the peak of the current values was seen after adding E. bieneusi DNA, confirming formation of DNA—ssDNA complex. A limit of detection (LoD) of 0.06 pg mL-1 was obtained with a linear detection range 0.1–10 4 pg mL-1. The integration of Ti3C2 and AuNPs not only facilitates the effective immobilization of DNA, but also improves the overall electron transfer kinetics. In addition, the developed genosensor demonstrated excellent sensitivity and selectivity with a low LoD of 0.06 pg mL-1.